2005
DOI: 10.1074/jbc.m409577200
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Down-regulates Adenosine 2b Receptor-mediated Signaling and Short Circuit Current in the Intestinal Epithelia by Inhibiting the Expression of Adenylate Cyclase

Abstract: Adenosine is an endogenous signaling molecule that is highly up-regulated in inflammatory states. Adenosine acts through the A2b receptor, a G protein-coupled receptor that couples positively to G␣ s and activates ad-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 58 publications
3
30
0
Order By: Relevance
“…Consistent with these data, immunohistological studies have found decreased AC5/6 expression in surface, compared with crypt, epithelial cells in the murine colon (27), and biochemical studies have detected diminished total AC activity in differentiated villus cells compared with undifferentiated crypt epithelial cells (36). These results, along with those observed in interferon-␥-stimulated colon epithelial cells (26), indicate that AC isoform expression is dynamic and responsive to environmental cues. Importantly, the nature of the environmental stimulus determines the specificity of the AC isoform expression.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Consistent with these data, immunohistological studies have found decreased AC5/6 expression in surface, compared with crypt, epithelial cells in the murine colon (27), and biochemical studies have detected diminished total AC activity in differentiated villus cells compared with undifferentiated crypt epithelial cells (36). These results, along with those observed in interferon-␥-stimulated colon epithelial cells (26), indicate that AC isoform expression is dynamic and responsive to environmental cues. Importantly, the nature of the environmental stimulus determines the specificity of the AC isoform expression.…”
Section: Discussionsupporting
confidence: 60%
“…For example, interferon-␥ inhibits the expression of AC5 and AC7 and decreases cAMP synthesis (26). However, the impact of epithelial cell differentiation on AC isoform expression is not known.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These cells secrete chloride into the lumen in response to a broad spectrum of extracellular stimuli, including adenosine and cholera toxin, using calcium and cyclic nucleotides as intracellular mediators. [15][16][17][18] This chloride secretion establishes an osmotic gradient that draws sodium and water across the tight junction, resulting in net fluid secretion. [19][20][21][22] Under normal conditions, the undifferentiated crypt cells mature into mucin-secreting goblet cells and absorptive enterocytes that express nutrient and ion transporters as they proliferate and migrate to the villus tip (Fig.…”
Section: Small Intestinementioning
confidence: 99%
“…Inserts (0.4-m pore size; Costar, Cambridge, MA) were rested in wells that contained medium until steady-state resistance was achieved, as described (16,17). Caco2-BBe cells and HT29-Cl.19A cells were grown in Dulbecco's modified Eagle's medium, supplemented with 14 mmol/liter NaHCO 3 , 10% fetal bovine serum, and penicillin/streptomycin (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%